A Novel Approach for Transvenous Embolization of Dural Arteriovenous Fistula Using a Balloon and a Coil as Walls: Case Presentation - Kenji Fukutome; Shuta Aketa; Tsukasa Nakajima; Hiromichi Hayami; Hiromitsu Sasaki; Ryuta Matsuoka; Rinsei Tei; Yasushi Shin; Yasushi Motoyama (Case Reports in Vascular Medicine)
Background. Transvenous embolization (TVE) for dural arteriovenous fistula (DAVF) is difficult depending on an accessible route. Reported herein is a case of transvenous embolization using a balloon and a coil as “walls.” Case Description. A 56-year-old male patient presented with a 1-month history of mild motor aphasia. The magnetic resonance imaging showed a hemorrhagic lesion in his left temporal lobe, and the cerebral angiography showed a DAVF, with parasinus shunt points near the torcula and the left transverse sinus. Access to the shunt point was very difficult; however, TVE was performed using a balloon as a wall. Furthermore, all lesion embolization was possible using a coil as a wall. Conclusions. Using a balloon or coil as a wall during a TVE is useful.